Structural mechanics analysis on 3D printed metal layers on a dissimilar metal base - Ong, Jun Yu (Nanyang Technological University, 2023)
The demand for a wider range of properties and functionalities has led to more research and developments in the additive manufacturing industry. There has been a heightened interest in multi-material additive manufacturing of dissimilar metal alloys due to the potential of it satisfying the demand. While there is extensive research done on the additive manufacturing of SS316L and CuCrZr individually, limited research has been done on the selective laser melting of these materials in multi-material additive manufacturing.